O primado da percepção e suas possibilidades geográficas: migração internacional e a corporeidade em Merleau-Ponty - Guilherme Figueira Gomes Augusto (2024)
This work begins a discussion about the phenomenon of international migration, analyzed based on the logic of Maurice Merleau-Ponty's philosophy and the concepts he addresses. In addition to Merleau-Ponty's writings, it uses Bernard Lahire's sociology on an individual scale (SEI), by methodologically corroborating the analysis of just one migrant individual called Carlinhos. Through Carlinhos' narrative, of his departure from Mantenópolis (ES) to try a life in North America, the challenges and longings generated by his displacement bring the concepts of corporeality, perceived world and spatiality closer to geographical writings, in an interdisciplinarity between philosophy and humanistic geography. Such concepts allow us to understand migration beyond a mere movement in space, the objective of this text being to articulate the phenomenon of international migration from the perspective of a phenomenological perspective, constituting migration as an experience expressed in the body, changeable and requiring intersubjective interactions between subjects. It is concluded that migration occurs in the migrant individual, modifying their life trajectory and the lessons they learned, guiding their corporeality. Furthermore, it summarizes the manifestation of spatiality in the face of Carlinhos's affective availability, which postulates the power of spatiality to stipulate "available" experiences, of a material and immaterial order